Sentralisasi Manajemen Multi-Router MikroTik Berbasis Web Melalui REST API pada Lingkungan Virtualisasi - Azril Arfansyah; Dedy Kiswanto; Muhammad Iqbal Fahrezzi; Arion Pardede (PPPM Institut Teknologi Pagar Alam, 2026)
Conventional management of MikroTik-based network infrastructure still relies on desktop-bound applications such as Winbox and Command Line Interface (CLI) that require per-device manual configuration, causing operational inefficiencies and the inability to provide centralized real-time visibility. This study develops a web-based Network Management System (NMS) leveraging the built-in REST API of MikroTik RouterOS version 7 to automate and centralize the configuration and monitoring of multiple routers within a single dashboard. The system is built on a three-tier architecture: a React 19-based frontend with Vite bundler, a Node.js and Express.js-based backend proxy, and an SQLite database layer. Evaluation was conducted in two stages: Black Box Testing for module functionality validation, and quantitative performance testing covering API endpoint response times, concurrent throughput, and multi-router scalability simulation. Results indicate that all 17 main API endpoints respond with an average time of 18.69 ms and a request success rate of 100% out of 1,404 total requests, with a communication failure rate of 0.00%. Scalability tests with 1 to 30 routers demonstrate sub-linear time growth through parallel and asynchronous execution mechanisms, with a total processing time of 185.98 ms for 30 simultaneous routers and a parallelization efficiency of 2.92x. The primary contribution of this study is the empirical demonstration that a Node.js proxy architecture exploiting RouterOS v7 REST API effectively scales multi-router configuration operations with measurable efficiency, while simultaneously integrating WireGuard VPN automation with server-side cryptographic management in a single platform.